La gestión del riesgo crediticio y su influencia en el control de la morosidad en la Cooperativa León XIII 2013 - 2016. - Gomez Gutierrez, Ivan (2019)
ABSTRACT The General Objective of this investigation was to determine the influence of Credit Risk Management in the Control of the delinquency of the Leon XIII 2013-2016 Cooperative, it is longitudinal and assumes the hypothesis that there is a positive relationship between both variables. The population is represented by all the personnel of the credit area (N = 40 workers. A questionnaire was designed to measure the relationship between both variables, and the reliability of the instrument is validated with a very high Cronbach's Alpha indicator (0.814); Credit risk factors could be identified: Application of customer identification procedures, Identification and relationship of linked accounts, Identification of origin of funds, Crossing of commercial references, Conservation of records and archiving for 10 years, Supervised procedures, Preparation of manuals, Assistance to information events. The objective of Identifying the factors that affect the Control of delinquency was met: Information security policies, List of High Risk Portfolios, Application of risk-based internal audit mechanisms, Generation of daily portfolio reports, Statistics of placements, evaluation of recoveries, surprise evaluations, distribution of documentation, procedures of adequate controls. It is concluded that the management of credit risk has a positive influence on the control of delinquency, there being a high positive correlation among the variables. Finally, it is recommended: Frequently monitor the factors of the Credit Risk Management of the Cooperative. To do this, the evaluation tool presented here (Questionnaire) itself must be complemented with the analysis of EEFF.